Modeling Heterogeneity in the Satisfaction, Loyalty Intention, and Shareholder Value Linkage: A Cross-Industry Analysis at the Customer and Firm Levels. (February 2016) - Larivière, Bart; Keiningham, Timothy L.; Aksoy, Lerzan; Yalçin, Atakan; Morgeson, Forrest V.; Mithas, Sunil
This study examines the relationship between customer satisfaction, loyalty intention, and shareholder value at the firm and individual customer levels. The authors also explore industry differences by using a multilevel and random-effects approach in which individual customer scores are nested within firm-level data and the estimated interrelationships are treated as random coefficients that are explained by industry characteristics. They compile a unique and detailed data set, which covers 10 years of information on 137 firms and includes a matched sample of 189, 069 customers from multiple sources, such as the American Customer Satisfaction Index, the Center for Research in Security Prices, and Compustat, to yield three important insights. First, aggregate firm-level effects may overestimate the impact that satisfaction has at the individual customer level. Second, a consideration of loyalty intention or repurchase intention as the mediator can improve our understanding of the satisfaction–shareholder value relationship and the fact that this relationship can vary across firms. Finally, the influence of satisfaction and loyalty intentions on shareholder value varies by industry. The authors discuss implications of findings for researchers, managers, and investors.